Wearable-Integrated Education and Its Association with Self-Management and Quality of Life Among Patients with Hypertension: A Quasi-Experimental Study - Sudarman, Sudarman; Asfar, Akbar; Asnaniar, Wa Ode Sri; Siokal, Brajakson; Ratniwati S, Wa Ode (Jurnal Pendidikan Keperawatan Indonesia, 2026)
Introduction: Hypertension is a leading global health concern requiring sustained self-management to prevent complications and improve quality of life. While digital health interventions are increasingly adopted, evidence on the effectiveness of wearable-integrated education in hypertension management remains limited.Objective: This study aimed to evaluate the effectiveness of wearable-integrated education on self-management behaviors and quality of life in patients with hypertension.Methods: A quasi-experimental study was conducted with 200 hypertensive patients recruited from community health centers. Participants were allocated into an intervention group (n = 100), which received wearable-integrated educational modules providing personalized feedback and reminders, and a control group (n = 100), which received standard health education. Outcomes included self-management, measured using the Hypertension Self-Management Behavior Questionnaire (HSMBQ), and quality of life, assessed with the WHOQOL-BREF. Descriptive, correlation, and multivariate regression analyses were performed.Results: Participants had a mean age of 54.2 years (SD = 9.1), with no significant baseline differences between groups. Post-intervention, the intervention group reported significantly higher self-management scores (78.4 ± 8.6 vs. 70.2 ± 9.1; p 0.001) and quality of life scores (82.6 ± 10.2 vs. 75.1 ± 11.0; p 0.001) compared with controls. Correlation analyses indicated that higher education, shorter duration of hypertension, and intervention participation were positively associated with outcomes. Multivariate regression confirmed the intervention as an independent predictor of both self-management (β = 0.39, p 0.001) and quality of life (β = 0.36, p 0.001), with models explaining 29% and 26% of the variance, respectively.Conclusion: Wearable-integrated education significantly improves self-management behaviors and quality of life among hypertensive patients. These findings highlight the potential of integrating wearable technology with educational strategies as a scalable, community nursing–driven approach to hypertension management